ARKAISME SPIRITUAL DALAM TRADISI LISAN BUDAYA CAHYANA - yana ervitaputri (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Universitas Islam Negeri Profesor Kiai Haji Saifuddin Zuhri Purwokerto Purwokerto, 2016)
This paper contains a study of oral tradition or folklore and context with the Islamization of Java, Central part of the period of the eleventh century to the fifteenth century in former Perdikan Cahyana which is geographically located in District Karangmoncol (13 villages) and the District of Rembang (8 Village) in Purbalingga Province Central Java. Philosophically this paper tried reassembling the historicity of archaism oral tradition is very important in establishing the meaning interpretation thus making present as values (spirit). The discussion in the socio-cultural studies methodically parsed based on the spatial chronology of the historical and narrative.The viewpoint of reviews using the analytical tools of philosophy, hermeneutics, sosioantropologis and geohistoris. A verification study using literary techniques either in the form of collection of published sources and interviews with sources and the practice of direct experience through observations.